A study of factors and their influence on mathematics-related beliefs and performance in Turkey - Kandemir, Mehmet Ali; Eryilmaz, Nurullah; Shelley, Mack (Frontiers in Education, 2024)
The present study endeavours to uncover the intricate nexus among pertinent variables, including self-efficacy, perceived usefulness, parental education levels, and gender, and their relationship with mathematics performance. To achieve this objective, several hypotheses were tested, and a path model was estimated. The study cohort comprised 117 8th-grade students (64 females, 53 males) enrolled in a secondary school in Turkey. Results, in general, supported research hypotheses and the path model. Males' mathematics self-efficacy was found to be higher than females. No significant gender difference was found in the mathematics performance score in the initial analysis. Nevertheless, gender made a significant contribution to the prediction of mathematics performance beyond the effects of other variables in the hierarchical regression analysis. Consistent with theoretical predictions, females' mathematics self-efficacy expectations were unrealistically low compared to males. However, the